PERLINDUNGAN HUKUM TERHADAP ANAK YANG MENJALANI PIDANA PENJARA DI LEMBAGA PEMASYARAKATAN - Indah Dwi Lestari Martha, Putu; Keneng, I Ketut; Sudjana, I Ketut (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 04, Juni 2013, 2013)
Indonesia with a variety of issue, all of which are so complex and form a chain of related and cannot be disconnected, leaving a tragic story about the fate of the nation’s children. So that not a few children who become criminals. In Act. No. 23 of 2002 regarding Child Protection, children who commit offenses termed children in conflict with the law. Sentenced to prison will be placed in penitentiary child, as provided for in Article 60 in Act No. 3 of 1997 regarding Juvenile Justice. Children who are placed in these prison vulnerable to violence, because it is outside the family (on the scope of authority of state institutions), that requiring protection (protection).
Keywords: Legal Protection, Children, Imprisonment, Penitentiary